2018
DOI: 10.1590/1678-457x.17117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of direct adding oregano essential oil (Origanum syriacum L.) on quality and stability of chicken meat patties

Abstract: Evaluate of Origanum syriacum L. essential oil grown in Jordan, and other comparable antioxidant on TBARS, total carbonyl, color values, and sensory attributes of raw chicken meat was investigated. Six treatments were prepared: (1) control (no additive); (2) 100 ppm oregano essential oil (DE); (3) 150 ppm DE; (4) 300 ppm L-ascorbic acid (E-300); (5) 5 and 14 ppm butylatedhydroxyanisole (BHA/E-320) for both breast and thigh meat respectively, and 6) 150 ppm Sodium nitrite (E-250), were prepared using ground chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…The result of the a-value of the beef samples in this study are shown in Table 3, with the value progressively decreasing across the days of storage within the treatments. This is in agreement with other studies who have reported remarkable decrease in redness intensity of meat samples (beef, mutton, and chicken) treated with essential oil during cold storage period [28, 30, 31]. At day 0, meat sample treated with 6% sweet basil EO had the highest redness values (19.18), followed by sample containing 4% (18.71) and 2 (18.45) sweet basil EO and least in control (17.89).…”
Section: Resultssupporting
confidence: 93%
“…The result of the a-value of the beef samples in this study are shown in Table 3, with the value progressively decreasing across the days of storage within the treatments. This is in agreement with other studies who have reported remarkable decrease in redness intensity of meat samples (beef, mutton, and chicken) treated with essential oil during cold storage period [28, 30, 31]. At day 0, meat sample treated with 6% sweet basil EO had the highest redness values (19.18), followed by sample containing 4% (18.71) and 2 (18.45) sweet basil EO and least in control (17.89).…”
Section: Resultssupporting
confidence: 93%
“…Oregano essential oil significantly reduced ( p <0.05) lipid and protein oxidation, and improved color stability of raw and cooked ground chicken breast meat, showing the strongest effect for all parameters at 400 ppm . A similar study has been conducted with O. syriacum L. EO showing 150 ppm as effective dose to delay lipid and protein oxidation . The effects of homogenization of oregano, sage and rosemary EOs with minced beef (2 % w/w) with respect to lipid oxidation and color properties during refrigerated storage were evaluated by Unal and coworkers .…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…[319] A similar study has been conducted with O. syriacum L. EO showing 150 ppm as effective dose to delay lipid and protein oxidation. [320] The effects of homogenization of oregano, sage and rosemary EOs with minced beef (2 % w/w) with respect to lipid oxidation and color properties during refrigerated storage were evaluated by Unal and coworkers. [321] Thyme and especially oregano EOs show capacity of suppress biogenic amines formation in refrigerated vacuum packed fillets of carp prolonging their shelflife up to five times than suggested by the manufacturers.…”
Section: Uses Of Eos In the Food Industriesmentioning
confidence: 99%
“…However, researchers still need to investigate their effective level, how it interact in meat system. Rosemary extract and (OE) is one of the most popular natural additives have been tested in different food recently (Liu et al, 2009;Haile, 2015;Pereira et al, 2017;Al-Hijazeen, 2018). These medical plants extracts were evaluated directly through meat surface as (Velasco & Williams, 2011;Kumar et al, 2015;Zhai et al, 2018), mixing in ground meat (Ahn et al, 2007;Al-Hijazeen, 2014;Al-Hijazeen et al, 2016a, b;Zahid et al, 2018;Manessis et al, 2020), indirectly in the animal feed (Botsoglou et al, 2003;Ri et al, 2017;Sierżant et al, 2018;Cázares-Gallegos et al, 2019), and it mostly showed positive effect enhancing meat quality and extended their shelf-life.…”
Section: Introductionmentioning
confidence: 99%
“…However, Origanum syriacum L. and Rosmarinus officinalis Linn. extract (Grown under Jordanian Climate conditions) were characterized with a high level of phenolic compounds (Ibrahim et al, 2012;Hudaib et al, 2015;Al-Hijazeen, 2018;Al-Hijazeen & Al-Rawashdeh, 2019). Generally, the antioxidant effect of these plants extracts are based on their phenolic compounds (Brewer, 2011;Shah et al, 2014).…”
Section: Introductionmentioning
confidence: 99%